Analisis Yuridis Potensi Perubahan Nomenklatur Serta Bentuk Hukum Bank Pembangunan Daerah Kalimantan Barat Literature Review: Juridical Analysis Of Potential Changes In The Nomenclature And Legal Form Of The West Kalimantan Regional Development Bank - Pratama, Yogi; Hamdani, Hamdani (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Perseroda West Kalimantan Regional Development Bank or "Perseroda Bank" is a Regional Company Company, West Kalimantan Regional Development Bank which will be formed based on the provisions of this PERDA Regional Companies are all companies whose capital is wholly or partially constituted as excluded regional assets, unless otherwise determined by or based on law. The aim of Regional Companies is to participate in implementing Regional development, especially in national economic development, to meet the needs of the people by prioritizing peace and enjoyment of work within the company, towards a just and prosperous society. Management of Regional Companies is in the hands of Regional Company administrators who are responsible to the Regional Head, the responsibility of the Regional Head is as owner and manager.